La tenencia compartida en la legislación ecuatoriana y el derecho a una vida digna de los niños, niñas y adolescentes - Vásquez Cumbicus, Nicole Salome (2025)
The present research has been developed on the basis of shared custody, which is a legal mechanism that guarantees both parents a participation and consequently a better attention with the objective of satisfying the interests and needs of the child and adolescent. Shared custody consists of a new way of exercising parental responsibility after a crisis in the marital relationship. Through this custody, both parents agree to establish an amicable relationship between them, based on respect, understanding and help to establish frequent and equitable communication with their children and to share in a fair and proportional manner the attention that the material needs of the children deserve, thus providing for the resolution of any disagreement that may arise in the future. The methodological design was adapted to the qualitative paradigmatic modality, since the aim is to solve problems of a social legal nature, using the historical-logical, analytical-synthetic, inductivedeductive methods, based on the analysis of a practical case, This will allow minors togrow up in a favorable environment, as well as to achieve that judges issue favorable resolutions in these processes, that is to say, in equal conditions and opportunities for both parties, and above all for the minor.